Enhancing internal audit independency and effectiveness in South Africa - Khumalo, Nkosinathi Eric (My University, 2019)
The purpose of the study is to review the second addition of Internal Audit Framework published by National Treasury of South Africa; which stipulates minimum guidelines for the establishment and operation of internal audit function in the public sector. The focus of the study is on the establishment and functioning of the internal audit in State-owned Entities. The findings and recommendations identified during the study are the basis for amending the framework. The internal audit function has a vital role to play in the enforcement of good corporate governance within State-owned Entities. This role can only be fulfilled if an internal audit is independent and objective. The independence and objectivity of the internal audit is largely influenced by the reporting lines. The Internal audit should functionally report to the Audit Committee, which is a sub-committee of the accounting authority/board of directors. The audit committee should be independent from management of the State-owned Entities, to ensure they assist the accounting authority to exercise its oversight over the integrity of the annual financial statements and the effectiveness of assurance functions within the institution. The accounting authority should appoint members to the audit committee. One of the members of the audit committee should Page 3 of 59 be a finance expert. Management should not recommend nor be involve in the appointment of audit committee members. The Audit committee should be responsible for the appointment of the Chief Audit Executive and setting up of his/ her job description on which performance reviews will be conducted on a periodical basis. The Audit committee should approve the internal audit charter and annual internal audit plan. Audit committee should periodically review the feedback on internal audit activities and obtain a confirmation from the Chief Audit Executive that the internal audit activities are independent. The independency of an internal audit is the freedom from unwarranted influence, it enables internal auditors to be objective and apply impartial, unbiased attitudes and professionalism when performing internal audit activities, which leads to the effectiveness of the internal audit function that is measured by the value it is adding to the organisation
MBA
Keywords: Auditing, Internal -- South Africa. Financial services industry -- South Africa.